Pengaruh pelatihan online dan pengembangan karier terhadap kinerja karyawan - Anisah, Diyah Nia; Dewie Tri Wijayati Wardoyo (Jurnal Ilmu Manajemen, 2025)
Employee performance is a crucial factor that determines an organization's success in achieving its goals. This study aims to analyze the influence of online training and career development on employee performance at one of the state-owned enterprises in the financial services sector, specifically at a branch office located in Sidoarjo. This study employs a quantitative approach. The sampling technique used is a census (saturation sampling), where all 33 permanent employees at PT Pegadaian Branch Office Sidoarjo serve as research respondents. Data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that, partially, online training does not have a significant impact on employee performance. Conversely, career development was found to have a positive and significant impact on employee performance. Simultaneously, online training and career development together were proven to have a significant impact on employee performance at PT Pegadaian Branch Office Sidoarjo. This study reinforces existing theory and provides practical implications for the management of PT Pegadaian Sidoarjo Branch Office to evaluate and align career development policies to be more fair and responsive. The aim is to ensure equal opportunities for all levels of employees, which will ultimately improve overall organizational performance through data-driven human resource management